Combusition Of Chlorinated VOCs Using Bimetallic Chromium-Copper Supported Over Modified H-ZSM-5 Catalyst. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2004)
The performance of chromium-copper supported over H-ZSM-5(Si/Al=240) modified with silicon tetrachloride (Cr10Cu0.5/SiCl4-Z) as the catalyst in the combustion of chlorinated VOCs (Cl-VOCs) is reported.